Quran-Based Early Childhood Education Management - Hasbullah, Hasbullah; Sanusi, Ahmad Sanusi (JURNAL PENELITIAN KEISLAMAN, 2023)
One of the problems that the Indonesian education is facing is the crisis of character. The lack of religious understanding is one of the factors that trigger the crisis of character. Therefore, strengthening religious education is one of the concrete steps to alleviate the crisis. PAUD Tahfidz al-Kautsar is one of the early childhood education institutions that provides education with a focus on strengthening the understanding and internalization of Islamic values and teachings for the prevention and mitigation of future character crisis. This institution implements Qur’an based learning. This research investigated how PAUD Tahfidz al-Kautsar is implementing Qur’anic based early childhood education. The research is a qualitative study in nature with the main informants being the head of the foundation, the director of the school, and the teachers of the school. Direct observation, documentation and in-depth interviews with informants were used to collect data.